Empowering local citizens to monitor their environment - Tilahun, Seifu A.; Atampugre, Gerald; Tall, Maimouna (International Water Management Institute, 2024)
Discover how the Citizens Science Initiative empowers local communities from Ahafo Ano Southwest District of Ghana to become active participants in water management and sustainability. This video highlights innovative approaches and success stories from the initiative, showcasing how citizen engagement is transforming in an inclusive landscape management plan. Join us on this journey of collaboration, education, and impact.